2022
DOI: 10.1002/rra.4063
|View full text |Cite
|
Sign up to set email alerts
|

Low‐head dam removal increases functional diversity of stream fish assemblages

Abstract: Despite the growing number of dam removals, few have been studied to understand their impacts on stream fish communities. An even smaller proportion of dam removal studies focus on the impacts of low‐head dam removals, although they are the most common type of dam. Instead, the majority of removal studies focus on the impacts of larger dams. In this study, two previously impounded Illinois Rivers were monitored to assess the impacts of low‐head dam removal on the functional assemblage of stream fishes. Study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Although we found significant changes in some habitat variables at above the dam site, the exact mechanisms underlying this change could not be identified in our study. Other studies found similar shifts in assemblage structure at impounded sites after dam removal and suggested habitat alteration as the driver of the observed change in assemblage structure (Hogg et al, 2015;Jones et al, 2022;Maloney et al, 2008;Poulos et al, 2014). We observed no significant change in assemblage structure at the control sites on Three and Twenty Creek coincident with the timing of dam removal in Twelvemile Creek, suggesting that dam removal and subsequent change to habitat characteristics were the drivers of the change in assemblage structure observed in Twelvemile Creek.…”
Section: Shifts In Assemblage Structuresupporting
confidence: 74%
See 2 more Smart Citations
“…Although we found significant changes in some habitat variables at above the dam site, the exact mechanisms underlying this change could not be identified in our study. Other studies found similar shifts in assemblage structure at impounded sites after dam removal and suggested habitat alteration as the driver of the observed change in assemblage structure (Hogg et al, 2015;Jones et al, 2022;Maloney et al, 2008;Poulos et al, 2014). We observed no significant change in assemblage structure at the control sites on Three and Twenty Creek coincident with the timing of dam removal in Twelvemile Creek, suggesting that dam removal and subsequent change to habitat characteristics were the drivers of the change in assemblage structure observed in Twelvemile Creek.…”
Section: Shifts In Assemblage Structuresupporting
confidence: 74%
“…Restoration via dam removal assumes that the ecological benefits will outweigh the ecological disturbance and economic cost caused by dam removal (Thomson et al., 2005). Despite the possible negative effects, over 1900 dams have been removed in the United State since 2000, yet relatively few studies document the effect of dam removal on fish populations or use carefully collected pre‐ and post‐removal data (American Rivers, 2019; Bellmore et al., 2017; Jones et al., 2022). Small‐dam removal studies are underrepresented in the literature and most dam‐removal studies are short‐term (1–2 years), with only 5% of studies longer than 5 years (Bellmore et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional ecology offers a powerful framework to better understand the causes and consequences of species-environment relationships (Southwood, 1977;Townsend and Hildrew, 1994;Violle et al, 2007) with countless implications in conservation biology and restoration ecology. It is a common practice in dam removal projects to investigate changes in the functional characteristics of fish communities (Shaffer et al, 2018;Jones et al, 2023), aquatic macroinvertebrate communities (Pollard and Reed, 2004;Hansen and Hayes, 2012;Kil and Bae, 2012;Poulos et al, 2019;Mahan et al, 2021), and riparian vegetation (Foley et al, 2017). In the present study, we explored taxonomic changes of these three communities as a first step to report ecosystem recovery after dam removal.…”
Section: Functional Recovery and Implications For Species Interaction...mentioning
confidence: 99%
“…Those that have, primarily described changes in the river community using perhaps more basic metrics such as community composition, species richness, abundance or density (e.g., Catalano et al, 2007;Stanley et al, 2007;Maloney et al, 2008;Burroughs et al, 2010;Kornis et al, 2015;Magilligan et al, 2016;Poulos and Chernoff, 2017;Bubb et al, 2021). Furthermore, such studies often used methods that have provided information regarding only a snap-shot in time and/or space such as electrofishing, hydroacoustics, snorkeling or eDNA (e.g., Dorobek et al, 2015;Hogg et al, 2015;Duda et al, 2020;Scherelis et al, 2020;Huang et al, 2023;Jones et al, 2023;Kiffney et al, 2023;Whittum et al, 2023) and were often narrowly-scoped temporally, spatially or both (Bellmore et al, 2017;Foley et al, 2017;Whittum et al, 2023). These methods may not fully reflect fish responses, and do not reveal any direct information about fish movement and timing.…”
Section: Introductionmentioning
confidence: 99%